The relationship between polycystic ovary syndrome and coronary heart disease: a bibliometric analysis - Liang, Xuzhi; He, Haijing; Zeng, Hao; Wei, Liuyi; Yang, Jiahuang; Wen, Yuqi; Fan, Siqi; Fan, Jiangtao (Frontiers in Endocrinology, 2023)
Abstract Background: Polycystic ovary syndrome (PCOS) is one of the most common gynecological endocrine diseases for women of puberty and reproductive age. PCOS can affect women’s health for the rest of their lives since the incidence of coronary heart disease (CHD) may increase in the perimenopausal and senile periods among PCOS women compared with non-PCOS women. Method: A literature retrieval based on the Science Citation Index Expanded (SCI-E) database. All obtained records results were downloaded in plain text format for subsequent analysis. VOSviewer v1.6.10, Citespace and Microsoft Excel 2010 software were utilized for analyzing the following terms: countries, institutions, authors, journals, references and keywords. Results: There were 312 articles retrieved from January 1, 2000 to February 8, 2023, and the frequency of citations was 23,587. The United States, England, and Italy contributed the majority of the records. Harvard University, the University of Athens, and Monash University were the top 3 most productive institutions with publications on the relationship between PCOS and CHD. Journal of clinical endocrinology & metabolism ranked first with the highest publications (24 records), followed by Fertility and sterility (18 records). The keywords were divided into six clusters in the overlay keywords network: (1) the correlation between CHD risk factors and PCOS women; (2) the relationship between cardiovascular disease and female reproductive system hormone secretion; (3) the interaction between CHD and metabolic syndrome; (4) the relationship between c-reactive protein and endothelial function and oxidative stress in PCOS patients; (5) the potential positive effect of metformin on reducing CHD risk factors in PCOS patients; (6) the study of serum cholesterol and body-fat distribution in patients with CHD in PCOS. Oxidative stress, genome-wide association, obesity, primary prevention, and sex difference were main hotspots in this field in recent five years according to the keyword citation burst analysis. Conclusion:The article obtained the hotspots and trends and provided a reference for subsequent research on the association between PCOS and CHD. Moreover, it is hypothesized that oxidative stress and genome-wide association were frontier hotspots in studies that explore the relationship between PCOS and CHD, and prevention research may be valued in the future.